Empreendedorismo e gênero: uma análise das percepções de mulheres empreendedoras - Veron, Samara Olartechea (Universidade Federal de São Carlos, 2025)
Entrepreneurship has been growing as an alternative to salaried employment in Brazil, consolidating a work culture adapted to conditions of unemployment and insecurity, in which workers individually assume responsibility for all risks. For women, entrepreneurship is presented not only as a way to reconcile productive and reproductive spheres, due to the flexibility of working hours, but also as a means of confronting gender inequalities in the world of work. The aim of this study is to investigate the perceptions of women entrepreneurs in São Carlos regarding the reconciliation between the demands of entrepreneurship and care work. To this end, we employed a semi-structured interview methodology with ten local women entrepreneurs. The analysis of the interviews revealed a duality in flexibility: on the one hand, it provides greater freedom in organizing work routines to meet care obligations; on the other, it intensifies working hours, leading women to assume multiple roles and making it difficult to delineate the boundaries between these two spheres. Thus, although entrepreneurship is presented as a solution to break with gender inequalities in work, these women continue to perform traditional gender roles and experience an intensification of work.
Entrepreneurship and gender: an analysis of women entrepreneurs’ perceptions
Keywords: Empreendedorismo; Empreendedorismo feminino; Gênero; Precarização do trabalho; Entrepreneurship; Female entrepreneurship; Gender; Precarization of work; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; 8. Trabalho Decente e Crescimento Econômico; 5. Igualdade de Gênero